28.4k views
7 votes
Write as a product: 25a2−0.01b10

1 Answer

7 votes

Answer:

We conclude that:


25a^2-0.01b^(10)=\left(5a+0.1b^5\right)\left(5a-0.1b^5\right)

Explanation:

Given the expression


25a^2-0.01b^(10)

Rewrite
25a^2-0.01b^(10) as
\left(5a\right)^2-\left(√(0.01)b^5\right)^2

so


25a^2-0.01b^(10)=\left(5a\right)^2-\left(√(0.01)b^5\right)^2

Apply difference of two squares formulas:


x^2-y^2=\left(x+y\right)\left(x-y\right)

so


\left(5a\right)^2-\left(√(0.01)b^5\right)^2=\left(5a+√(0.01)b^5\right)\left(5a-√(0.01)b^5\right)


=\left(5a+0.1b^5\right)\left(5a-0.1b^5\right)
√(0.01)=0.1,

Therefore, we conclude that:


25a^2-0.01b^(10)=\left(5a+0.1b^5\right)\left(5a-0.1b^5\right)

User Hrickards
by
5.5k points